Estudo do risco coronariano em mulheres no período do climatério - Dallazen, Fernanda (2016)
Introduction: With the female aging process, the climacteric is a key stage in the women s lives, in which there is a decrease in sex hormones, a change of distribution in body fat and changes in lipid profile involving the increase of coronary risk in women. Objective: To evaluate the coronary risk in women in the climacteric period using the Conicity Index. Methods: A cross-sectional study, not probabilistic, linked to the research "Female Aging Study" from the Regional University of the Northwest of Rio Grande do Sul State - UNIJUI approved by the Research Ethics Committee of UNIJUI under opinion No. 864,988 / 2014 and CAAE 37096614.0 .0000.5350. The study consists of women between 35-65 years of age enrolled in the Family Health Strategy in the urban area of the city of Ijuí, RS (Brazil). Data collection was conducted from 2014 to 2016 and the variables of interest were sociodemographic and health conditions; assessment of nutritional status; clinical evaluation with measurement of blood pressure; and biochemical evaluation; coronary risk was assessed using the C-Index. The women were divided into two groups considering the phase of the climacteric, G1: premenopausal women and G2: postmenopausal women. Results: Comprising 102 women, mean age 51.5 ± 7.9 years old, 40.2% of these (41) belonging to G1 and 59.8% (61) to G2. It was observed a statistical difference between G1 and G2 in relation to waist circumference, body fat%, LDL-cholesterol, total cholesterol, fasting glucose, systolic blood pressure and Conicity Index. In addition, the G2 has higher averages in most variables compared to G1. The average taper Index in both groups showed a high coronary risk in women in the study. By analyzing the variables G1 considering coronary risk low and high is observed statistically significant differences for: body weight, waist circumference, body mass index, triglycerides, diastolic blood pressure and Conicity Index; in G2 for waist circumference, body mass index, body fat percentage, glucose and Conicity Index. In the analysis of coronary risk between G1 and G2 it was found p≤0,05 value for coronary risk, low waist circumference, percentage of body fat and taper index; already with high coronary risk was observed between the percentage of body fat, LDL-cholesterol, total cholesterol, fasting glucose and Conicity Index. Conclusion: Women in G2 showed the highest coronary risk when compared to the women in G1, although these ones already show high coronary risk. In addition, women showed changes in anthropometric, lipid and glycemic profile with the arrival of the climacteric period, being the taper index a good predictor of coronary risk. This way, it is necessary the expansion of targeted assistance for women in climacteric period with a view to support therapeutic decision making in primary health care.